Penerapan Sistem Kriptografi Enkripsi Jamak dan Tanda Tangan Digital Dalam Mendukung Keamanan Informasi - Chyan, Phie (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2018)
The use of cryptographic techniques and digital signatures is widely applied as a method to secure confidentiality and authenticity of data such as sending data over the internet network. on cryptographic, data that intent to be secret is disguised by changing the original data to unreadable format while the digital signature is used to check the authenticity of the message according to the source. Both of these techniques have weaknesses, but by combining these two techniques it will make confidential data more secure in secrecy and authenticity. The main discussion of this research is to create a data security application by combining cryptographic techniques and the use of digital signatures. The algorithm used is a Multi- encryption algorithm consisting of a combination of substitution and transposition algorithms and el gamal algorithm for document verification using digital signatures. The process that is done is to encrypt the message either typed directly into the application or from the text file that is loaded into the application. The results of this study are applications designed to meet information security needs, both protection against the confidentiality of information and protection against counterfeiting and changing unwanted information.Keywords: Cryphtograph, Multi-encryption, Digital Signature